2002
DOI: 10.1055/s-0037-1613352
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Effects of Anti-Glycoprotein Ib Antibodies on Megakaryocytes and Platelets

Abstract: SummaryAntibodies directed against the glycoprotein (GP) Ib have been identified as the potential cause of various platelet disorders: Immune thrombocytopenic purpura (ITP) may be caused by such autoantibodies; Anti-thrombotic drugs targeting GPIb also induce thrombocytopenia. In order to elucidate the potential mechanism(s) of the anti-GPIb effects, we have examined by electron microscopy (EM) the effect of several antibodies directed against GPIb and GPIIb-IIIa on human culture megakaryocytes (MK). Virtually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 32 publications
1
16
0
3
Order By: Relevance
“…This would be analogous to the in vitro inhibition described by others. 15,16 As such, proplatelet formation by megakaryocytes with increased GP Ib␣ antigen would be less inhibited, as would have occurred within the hTg Y605X marrow after the induction of thrombocytopenia ( Figure 3B). The net result would be an increased rate of circulating platelet recovery in the hTg Y605X animal.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This would be analogous to the in vitro inhibition described by others. 15,16 As such, proplatelet formation by megakaryocytes with increased GP Ib␣ antigen would be less inhibited, as would have occurred within the hTg Y605X marrow after the induction of thrombocytopenia ( Figure 3B). The net result would be an increased rate of circulating platelet recovery in the hTg Y605X animal.…”
Section: Discussionmentioning
confidence: 94%
“…14 However, a role for the extracytoplasmic domains of the complex cannot be excluded because antibodies to GP Ib-IX can alter proplatelet formation in vitro. 15,16 In addition, in vitro evidence links the expression of GP Ib-IX to cell proliferation, further suggesting the GP Ib-IX complex might regulate megakaryocyte growth. 17 The mouse phenotype mimicking Bernard-Soulier syndrome in humans can be rescued by expression of a human GP Ib␣ transgene under the control of a megakaryocytic gene promoter.…”
Section: Introductionmentioning
confidence: 99%
“…During maturation, MK express CD41/CD61 and CD42b/CD42a on their surfaces, 6,7,26 so it is likely that the binding of antiplatelet autoantibodies could inhibit MK maturation [27][28][29] and interfere with platelet release. During endomitosis, the ploidy of diploid (2N) MK precursors increases 30 and each of these mature MK is able to release thousands of platelets 31 by extending proplatelets.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 In some ITP patients platelet production is normal but in others it is decreased. 4,5 As megakaryocytes (MK) also express CD41/CD61 and CD42b/CD42a on their surfaces, 6,7 it has been proposed that antiplatelet antibodies might bind MK and cause their destruction, impair their function or delay their maturation and consequently interfere with platelet production. 8 In vitro studies showed that plasma from patients with ITP suppressed MK growth and/or maturation.…”
Section: Introductionmentioning
confidence: 99%
“…Verminderte Thrombozytopoese Bisher ging man davon aus, dass bei der ITP sowohl der ThrombozytenabbaualsauchdieNeubildungvonThrombozytenerhöhtsind.EinTeilderPatientenhatjedochzusätzlich zum vermehrten Thrombozytenabbau eine insuffiziente Thrombozytopoese [26][27][28].MöglicherweisestörendieAnti-körpergegenThrombozyten-GlykoproteineauchdieReifung derMegakaryozytenimKnochenmark [29][30][31][32][33].…”
Section: Einführung Definition Und Terminologieunclassified